Respiratory symptoms and pulmonary function in paint industry workers exposed to volatile organic compounds: A systematic review and meta-analysis. - Lavanya Sekhar; Akila Govindarajan Venguidesvarane; Gayathri Thiruvengadam; Yogita Sharma; Vidhya Venugopal; Santhanam Rengarajan; Priscilla Johnson (PLoS ONE)
Several epidemiological studies have examined the respiratory consequences of occupational exposure to volatile organic compounds (VOCs). However, their effects on paint industry workers in organised and unorganised occupational sectors vary. The present systematic review and meta-analysis aim at evaluating the respiratory symptoms and pulmonary function of paint industry workers from various occupational sectors exposed to VOCs. Relevant MESH terms were used for literature search in MEDLINE, Scopus, Web of Science, and Google Scholar till August 2023. The articles were independently retrieved and qualified by two reviewers and two subject experts arbitrated reviewer differences to establish relevant article inclusion. The systematic review comprised 23 observational studies that assessed respiratory symptom and pulmonary function tests (PFT) among paint industry worker from various occupational sectors. The meta-analysis included 12 studies on respiratory symptoms and 18 on PFT. Pooled meta-analysis was done using random effect model, and the crude odds of respiratory symptoms such as cough (OR: 2.72, 95% confidence interval [CI]: 1.74 to 4.25), dyspnoea (OR: 3.59, 95% CI: 2.13 to 6.05), nasal/throat irritation (OR: 4.5, 95% CI: 1.7 to 12.1), and wheezing (OR: 2.28, 95% CI: 1.37 to 3.82) were significantly higher among paint industry workers exposed to VOC compared to unexposed population. PFT parameters, such as forced expiratory volume in one second (FEV1) (SMD: -0.88, 95% CI: -1.5 to -0.2) and FEV1/forced vital capacity (FEV1/FVC) (SMD: -0.97, 95% CI: -1.6 to -0.32) were found to be significantly reduced among the paint industry workers. The meta-analysis has helped in generating evidence regarding the effect of VOC on respiratory symptoms and pulmonary function and the strength of the association varied with geographical regions, and the type of occupational sectors. Despite the heterogeneity (I2 > 75%) of studies, statistical power of this analysis was significant. Trial registration: PROSPERO registration number: CRD42022311390.